2018
DOI: 10.1186/s12974-018-1139-z
|View full text |Cite
|
Sign up to set email alerts
|

LncRNA H19 contributes to hippocampal glial cell activation via JAK/STAT signaling in a rat model of temporal lobe epilepsy

Abstract: BackgroundAstrocyte and microglia activation are well-known features of temporal lobe epilepsy that may contribute to epileptogenesis. However, the mechanisms underlying glia activation are not well understood. Long non-coding RNA (lncRNA) H19 has diverse functions depending on physiological or pathological state, and its role in epilepsy is unknown. We previously demonstrated that H19 was significantly upregulated in the latent period of epilepsy and may be associated with cell proliferation and immune and in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

9
76
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 107 publications
(85 citation statements)
references
References 32 publications
9
76
0
Order By: Relevance
“…Interestingly, we found that STAT3 protein acted as the target of miR‐519d, constituting the CASC9‐miR‐519d‐STAT3 axis. STAT3 acts as a transcription factor . With the assistance of bioinformatic JASPAR tool, STAT3 could also bind with the promoter region of lncRNA CASC9, in turn, promoting the transcription activity of lncRNA CASC9.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Interestingly, we found that STAT3 protein acted as the target of miR‐519d, constituting the CASC9‐miR‐519d‐STAT3 axis. STAT3 acts as a transcription factor . With the assistance of bioinformatic JASPAR tool, STAT3 could also bind with the promoter region of lncRNA CASC9, in turn, promoting the transcription activity of lncRNA CASC9.…”
Section: Discussionmentioning
confidence: 99%
“…STAT3 acts as a transcription factor. [26][27][28][29] With the assistance of bioinformatic JASPAR tool, STAT3 could also bind with the promoter region of lncRNA CASC9, in turn, promoting the transcription activity of lncRNA CASC9. Therefore, we conclude that CASC9 relieves the inhibition of STAT3 induced by miR-519d to recover STAT3 expression, reversely, STAT3 could activate the transcription activity of CASC9, forming the positive feedback loop of STAT3-CASC9-miR-519d-STAT3 axis.…”
Section: Discussionmentioning
confidence: 99%
“…20 Previous studies also have indicated that lncRNAs, H19 and UCA1, may be involved in the pathogenesis of SE via regulation of immune and inflammatory responses, cell apoptosis, activation of MAPK and NF-κB signalling pathway. [17][18][19] However, no study has been performed to investigate the expression profile of lncRNAs in SE.…”
Section: Knockdown Of Nonratt0107882 Inhibits Neuronal Apoptosismentioning
confidence: 99%
“…16 In SE, H19-a lncRNA-was demonstrated to contribute to epileptogenesis by aggravating SE-induced neuronal loss, glial cell activation, mossy fibre sprouting and cognitive impairments in epileptic rats. 17 Whole-transcriptome screening revealed that H19 exhibited diverse functions related to epileptogenesis, including demyelination, immune and inflammatory responses, cell apoptosis and activation of MAPK. 18 UCA1, another lncRNA, may participate in the pathogenesis of epilepsy, which is evidenced by the dynamic change in the expressions of UCA1 and NF-κB during epilepsy.…”
mentioning
confidence: 99%
“…Actually, the alternation of glial cells is strongly associated with the development of LTE [11] . A previous study shows that lncRNAs such as H19 promotes activation of hippocampal glial cells and serves as a therapeutic tool to prevent epileptogenesis by regulating JAK/STAT pathway [12] . The formation of glial fibrillary acidic protein (GFAP)-positive glia is realized by activation of JAK/STAT3 pathway [13] .…”
Section: Introductionmentioning
confidence: 99%